BILATERAL SERPIGINOUS-LIKE CHORIORETINITIS ASSOCIATED WITH CILIOCHOROIDAL MELANOMA: A Clinicopathologic Correlation. Issue 4 (April 2022) - Al-Moujahed, Ahmad; Lin, Jonathan H.; Gagnon, Michael R.; Pulido, Jose; Mruthyunjaya, Prithvi; Jung, Jesse J.
Abstract : Supplemental Digital Content is Available in the Text. Paraneoplastic serpiginous-like chorioretinitis may occur secondary to ciliochoroidal melanoma. Multimodal imaging correlating to histopathology and immunohistochemistry demonstrates that the chorioretinitis lesions had predominantly CD3/CD8 T-cell lymphocytic infiltration of the choroid with overlying retinitis. Abstract : Purpose: To report the clinicopathologic correlation of a case of bilateral serpiginous-like chorioretinitis (SLC) associated with unilateral ciliochoroidal melanoma. Methods: A 71-year-old white woman was diagnosed with progressive SLC in both eyes associated with ciliochoroidal melanoma in the right eye. Clinical findings and imaging before and after enucleation in the right eye were correlated to histologic and immunohistochemistry sections. Results: Examination and imaging identified a peripheral bilobed amelanotic lesion with low reflectivity on B-scan ultrasound with an associated exudative detachment in the right eye. Additionally, multiple areas of new SLC lesions in the macula and peripapillary region in the right eye and along the inferior arcade in the left eye were observed. Oncologic evaluation confirmed a Class 2, ciliochoroidal melanoma, and the eye was enucleated. Autoimmune and infectious laboratory evaluations for the etiology of the SLC lesions were negative. Histopathology of the enucleated eye confirmed the diagnosis of uveal melanoma with lymphocytic inflammation at the edges of the tumor itself and in the areas of discrete SLC lesions. Immunohistochemistry identified similar predominantly CD3 and CD8 T cells and fewer CD20 B cells in both regions. Conclusion: Serpiginous-like chorioretinitis may present as a paraneoplastic, predominantly T-lymphocyte inflammation associated with intraocular tumor such as uveal melanoma.